The death penalty on trial : crisis in American justice - Kurtis, Bill. (New York, NY : Public Affairs, 2004)
In Death Penalty on Trial, Kurtis takes readers on his most remarkable investigative journey yet. Together, we revisit two harrowing murder scenes, study the evidence and explore the tactical decisions made before and during trial, which sent two innocent men to death row. Through these cases, we encounter the eight main reasons why the wrong people are condemned to death, including overzealous and dishonest prosecutors, corrupt policemen, unreliable witnesses and expert witnesses, incompetent defence lawyers, bias judges and prison informants. We see why the new jewel of forensic science, DNA, is revealing more than innocence and guilt, opening a window into the criminal justice system that could touch off a revolution of reform. Ultimately we come to a remarkable conclusion: The possibility for error is simply too great to allow the death penalty to stand as its ultimate punishment.
Case 1: Ray Krone -- From the crime to the trial -- Life on death row -- Appeal -- How could this have happened? -- Case 2: Thomas Kimbell -- Crime -- Trial -- Appeal -- Conclusion -- Acknowledgments -- Index.
Includes index.
Includes bibliographical references and index.
Keywords: Capital punishment -- United States